2020
DOI: 10.18592/let.v10i2.4051
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Whatsapp App in Distance Language Learning in Pandemic Covid-19: A Case Study in Nahdlatul Ulama University of Yogyakarta

Abstract: Lately, pandemic covid-19 has changed the educational field including learning methods from conventional learning to distance learning. This shift needed more adaptation for all parts like stakeholders, teachers, and also students. Evidently, various efforts have been made by teachers in simplifying teaching and learning such as applying some digital technologies like WhatsApp App, an asynchronous communication to reach the students’ presence with any spaces and time. This study aimed to describe and to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 27 publications
2
16
1
Order By: Relevance
“…English language related studies during the Covid-19 process (between March 2020 and February 2021) (Aji et al, 2020;Allo, 2020;Almekhlafy, 2020;Andriivna et al, 2020;Ariyanti, 2020;Astuti & Solikhah, 2021;Atmojo & Nugroho, 2020;Bailey & Lee, 2020;Chiatoh & Chia, 2020;Dahmash, 2020;Davies et al, 2020;Destianingsih & Satria, 2020;Farrah & Al-Bakry, 2020;Fatima, 2020;Fitria, 2020;Forrester, 2020;Fuad et al, 2020;Fuentes Hernández et al, 2020;Gao & Zhang, 2020;Hadianti & Arisandi, 2020;Hafidz, 2020;Hakim, 2020;Hamid, 2020;Hartshorn & Mcmurry, 2020;Hazaea et al, 2021;Hodges et al, 2020b;Hopp & Thoma, 2020;Huang et al, 2021;Kamhi-Stein et al, 2020;Karakuzu et al, 2020;Karataş & Tuncer, 2020;Karim & Hasan, 2020;Kawinkoonlasate, 2020;Khafaga, 2021;Kholis, 2020;Krishan et al, 2020;Kusumawati, 2020;Li et al, 2020;Lie et al, 2020;Loo, 2020;…”
Section: Study Focus Authors Nmentioning
confidence: 99%
See 1 more Smart Citation
“…English language related studies during the Covid-19 process (between March 2020 and February 2021) (Aji et al, 2020;Allo, 2020;Almekhlafy, 2020;Andriivna et al, 2020;Ariyanti, 2020;Astuti & Solikhah, 2021;Atmojo & Nugroho, 2020;Bailey & Lee, 2020;Chiatoh & Chia, 2020;Dahmash, 2020;Davies et al, 2020;Destianingsih & Satria, 2020;Farrah & Al-Bakry, 2020;Fatima, 2020;Fitria, 2020;Forrester, 2020;Fuad et al, 2020;Fuentes Hernández et al, 2020;Gao & Zhang, 2020;Hadianti & Arisandi, 2020;Hafidz, 2020;Hakim, 2020;Hamid, 2020;Hartshorn & Mcmurry, 2020;Hazaea et al, 2021;Hodges et al, 2020b;Hopp & Thoma, 2020;Huang et al, 2021;Kamhi-Stein et al, 2020;Karakuzu et al, 2020;Karataş & Tuncer, 2020;Karim & Hasan, 2020;Kawinkoonlasate, 2020;Khafaga, 2021;Kholis, 2020;Krishan et al, 2020;Kusumawati, 2020;Li et al, 2020;Lie et al, 2020;Loo, 2020;…”
Section: Study Focus Authors Nmentioning
confidence: 99%
“…One of the most remarkable findings of this study is that Zoom, Google Meet and Microsoft Teams were also favoured for some of their default features, such as recording the sessions, which contributes to the flexibility of online teaching and learning, narrowing the power/status distance between students and teachers, and offering screen sharing opportunities and chat rooms (Destianingsih & Satria, 2020;Hamid, 2020;Wong, 2020). Apart from these, WhatsApp was also much favoured by students and WhatsApp created an online language community where language use continued even while everyone was staying at home during quarantine (Hadianti & Arisandi, 2020;Kholis, 2020). Findings also show that learning management systems such as Blackboard and mixed reality learning environments such as Mursion were reported to contribute positively to student learning during the pandemic (Almekhlafy, 2020;Hakim, 2020;Kamhi-Stein et al, 2020).…”
Section: Findings Of the Second Research Question Based On The Impact Of Covid-19 On English Language Teaching And Learning From The Globmentioning
confidence: 99%
“…More importantly, ERT granted students more interactions with their instructor and peers than their previous F2F learning. Kholis (2020) found that WhatsApp for distance asynchronous English learning provided diverse types of instructional resources (e.g., PDF, Word, Excel, PowerPoint, video, voice, pictures) that students had easy access to. Another study (Kang, 2020) investigated international students in universities in Canada and found that they are exposed to challenges such as difficult access to social and academic support from universities, online test anxiety, and the lack of academic writing and speaking support tailored for them during the pandemic.…”
Section: Emergency Remote Teachingmentioning
confidence: 99%
“…Researchers regarded online learning since the outbreak of COVID-19 as temporary access to learning and a replacement of physical classes. Existing research has investigated students' overall experiences of online education Dhawan, 2020;Mohmmed et al, 2020;Shim & Lee, 2020;Sun et al, 2020) or in several English specific contexts, such as EFL studies in China (Huang et al, 2021) and ESL in Indonesia (Kholis, 2020). However, there are limited reports on ESL students' engagement in speaking classes in Canada.…”
Section: Introductionmentioning
confidence: 99%
“…The WhatsApp application presents some features like group chat, text message, photo sharing, video sharing, and voice note. Kholis (2020) conducted research about the effectiveness of using WhatsApp in distance learning during a pandemic. The result from this study showed that the use of WhatsApp is effective and efficient during online learning.…”
Section: Introductionmentioning
confidence: 99%